In Vitro Study of Endothelial Cell Morphology and Gene Expression in Response to Wall Shear Stress Induced by Arterial Stenosis - Mu, Lizhong; Liu, Xiaolong; Liu, Mengmeng; Long, Lili; Chi, Qingzhuo; He, Ying; Pan, Yue; Ji, Changjin; Gao, Ge; Li, Xiaona (Frontiers in Bioengineering and Biotechnology, 2022)
Objectives We examined the correlation between changes in hemodynamic characteristics induced by arterial stenosis and vascular endothelial cell (EC) morphology and gene expression in straight silicone arteries. Materials and methods Transparent silicone straight artery models with four degrees of stenosis (0%, 30%, 50%, and 70%) were fabricated. Particle image velocimetry was performed to screen for silicone vessel structures with good symmetry and to match the numerical simulations. After the inner surface of a symmetric model was populated with ECs, it was perfusion cultured at a steady ﬂow rate. A computational fluid dynamics (CFD) study was conducted with the same perfusion conditions as in the flow experiment. The high WSS region was then identified by CFD simulation. EC morphology in the high WSS regions was characterised using confocal microscopy. ECs were antibody-stained to analyse the expression of inflammatory factors, including matrix metalloproteinase (MMP)-9 and nuclear factor (NF)-κB, which were then correlated with the CFD simulations. Results As the degree of vascular stenosis increases, more obvious jet flow occurs, and the maximum WSS position moves away first and then back. ECs were irregularly shaped at vortex flow regions. The number of gaps between the cells in high WSS regions increased. MMP-9 and NF-κB expression did not differ between vessels with 30% and 0% stenosis. When arterial stenosis was 70%, MMP-9 and NF-κB expression increased significantly, which correlated with regions of substantially high WSS in the CFD simulations. Conclusions Stenotic arteries induce hemodynamic stress variations, which contribute to differences in EC morphology and gene expression. A high degree of vascular stenosis can directly increase inflammatory factor expression.